2020
DOI: 10.1021/acs.chemmater.9b05273
|View full text |Cite
|
Sign up to set email alerts
|

Methylhydrazinium Lead Bromide: Noncentrosymmetric Three-Dimensional Perovskite with Exceptionally Large Framework Distortion and Green Photoluminescence

Abstract: Three-dimensional (3D) lead halide perovskites have emerged as a promising class of coordination polymers for solar cells, photodetectors, and light-emitting devices. These compounds thus far comprise methylammonium, formamidinium, or cesium as cations. In this work, we introduce a new methylhydrazinium 3D perovskite, CH3NH2NH2PbBr3, that crystallizes in the polar P21 structure at room temperature and undergoes a phase transition to the cubic Pm3̅m phase at 418 K. This perovskite exhibits strong second-harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
301
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(333 citation statements)
references
References 39 publications
10
301
1
Order By: Relevance
“…The remaining stretching vibrations, νasCNC, νsCNC and νNN, are located in the 990-1002, 820-832 and 1089-1098 cm −1 range, respectively. The position of the νsCNC bands is in good agreement with previous studies, i.e., this band was observed at 874 cm −1 for [MHy]Mn(HCOO)3 [20], 877 cm −1 for [MHy]Mn(H2POO)3 [42], 868 and 871 cm −1 for [MHy]PbBr3 [43] and 881 cm −1 for [MHy]PbCl3 [44]. The antisymmetric counterpart was previously observed at 1010 cm −1 for [MHy]Mn(H2POO)3 [42], 1004 cm −1 for [MHy]PbBr3 [43] and 1011 cm −1 for [MHy]PbCl3 [44].…”
Section: Room-temperature Ir and Raman Spectra And Assignment Of Bandssupporting
confidence: 91%
See 1 more Smart Citation
“…The remaining stretching vibrations, νasCNC, νsCNC and νNN, are located in the 990-1002, 820-832 and 1089-1098 cm −1 range, respectively. The position of the νsCNC bands is in good agreement with previous studies, i.e., this band was observed at 874 cm −1 for [MHy]Mn(HCOO)3 [20], 877 cm −1 for [MHy]Mn(H2POO)3 [42], 868 and 871 cm −1 for [MHy]PbBr3 [43] and 881 cm −1 for [MHy]PbCl3 [44]. The antisymmetric counterpart was previously observed at 1010 cm −1 for [MHy]Mn(H2POO)3 [42], 1004 cm −1 for [MHy]PbBr3 [43] and 1011 cm −1 for [MHy]PbCl3 [44].…”
Section: Room-temperature Ir and Raman Spectra And Assignment Of Bandssupporting
confidence: 91%
“…The position of the νsCNC bands is in good agreement with previous studies, i.e., this band was observed at 874 cm −1 for [MHy]Mn(HCOO)3 [20], 877 cm −1 for [MHy]Mn(H2POO)3 [42], 868 and 871 cm −1 for [MHy]PbBr3 [43] and 881 cm −1 for [MHy]PbCl3 [44]. The antisymmetric counterpart was previously observed at 1010 cm −1 for [MHy]Mn(H2POO)3 [42], 1004 cm −1 for [MHy]PbBr3 [43] and 1011 cm −1 for [MHy]PbCl3 [44]. For the [MHy]Mn(HCOO)3 crystal, this vibration was assigned to bands observed near 1092 cm −1 [20], but our DFT and previous ab initio calculations [41] showed that bands observed in the 1089-1098 cm −1 range for [DMHy]Mn(HCOO)3 originate from νNN.…”
Section: Room-temperature Ir and Raman Spectra And Assignment Of Bandssupporting
confidence: 91%
“…[ 9 ] Despite great efforts have been made to broad the 3D ABX 3 OIHP family, the resulting fruits were minimal. Recently, the [F‐CH 2 NH 3 ] + and [CH 3 NH 2 NH 2 ] + cations were utilized to form the 3D ABX 3 lead‐based OIHP [F‐CH 2 NH 3 ]PbBr 3 [ 10 ] and [CH 3 NH 2 NH 2 ]PbX 3 (X = Br or Cl), [ 11 ] respectively, but none of them shows the ferroelectricity. Discovering a new 3D ABX 3 OIHP semiconductor has been a great challenge, while endowing it with ferroelectricity is more arduous.…”
Section: Methodsmentioning
confidence: 99%
“…B represents cation locating in the center of octahedron, which could be Pb 2+ , Sn 2+ , and Ge 2+ in the more generalized cases of MHPs [2][3][4] but restricted to be Pb 2+ for LHPs. A represents the cation locating in the vacancy of neighboring octahedron cages, which could be either organic or inorganics: the inorganic examples include Cs + [5], while the organic examples include the methylammonium [6,7], formamidinium [8,9], and recently discovered methylhydrazinium [10,11]. It is expected that inorganic counterparts generally maintain better chemical stability than their organic counterparts [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to solar cells [1,13], the materials are also utilized in lasers [7,14], light emitting diodes (LEDs) [15][16][17], photodetectors [18][19][20], modulators [21][22][23], and so on. Moreover, the materials, especially those with bromides, are found to exhibit outstanding nonlinear properties [10,[24][25][26][27], thus demonstrating promising potential in applications such as imaging, optical limiting, and frequency conversion. Currently, people are incorporating the LHPs into waveguides and micro optical cavities, so as to further miniaturize the LHP-based devices.…”
Section: Introductionmentioning
confidence: 99%